Characteristics of lymphovascular metastatic spread in lung adenocarcinoma according to the primary cancer location - Kemal Grbić; Bakir Mehić (Medicinski glasnik, 2019)
Aim: To compare the localization of lung adenocarcinoma with tumour size and lymphovascular invasion (LVI) presence, and to determine the frequency of metastasis findings in hilar and mediastinal lymph nodes depending on the localization of the tumour and status of lymphovascular invasion. Method: This observational cross-sectional study included 261 patients with complete resection of confirmed lung adenocarcinoma. The dependence between categorical variables were performed with χ2 and Fisher's exact tests. A p<0.05 was considered as statistically significant. Result: Metastases to hilar lymph nodes at lung adenocarcinoma with central localization and presented lymphovascular invasion were more frequently found than tumours with peripheral localization (p<0.001). In tumours with peripheral localization, lymphovascular invasion was less frequent; even in tumours greater than 7 cm in the largest dimension the presence of LVI was not 100%. Metastases to mediastinal lymph nodes in tumours with central localization and presented lymphovascular invasion were less frequent than in tumours with peripheral localization and presented lymphovascular invasion (p=0.002). Conclusion: In invasive adenocarcinoma, lymphovascular invasion was much more common in centrally positioned than in peripherally positioned tumours. Metastases to the hilar and mediastinal lymph nodes, regardless of the findings of lymphovascular invasion, usually originated from upper lobe tumours.
Keywords: Frequency; relationship; post-resection histopathological findings; clinical pathological characteristics